A two-step strategy to identify episodic sources of gravitational waves and high-energy neutrinos in starburst galaxies - Allen, M. L.; Biermann, P. L.; Caramete, L. I.; Chieffi, A.; Chini, R.; Frekers, D.; Gergely, L. Á.; Harms, B.; Jaroschewski, I.; Joshi, P. S.; Kronberg, P. P.; Kun, E.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
Supermassive black hole mergers with spin-flips accelerate energetic particles through their precessing relativistic jets, producing high energy neutrinos and finally gravitational waves [Gergely & Biermann (2009), Kun et al. (2017), Kun et al. (2019), Kun et al. (2021)], and [Becker Tjus et al. (2022), Jaroschewski (2023a), Jaroschewski et al. (2023b)]. In star formation massive stars come in pairs, triplets and quadruplets, allowing second generation mergers of the remnants [Chini et al. (2012), Chini et al. (2013a), Chini et al. (2013b)] with discrepant spin directions. The Gravitational Wave (GW) data [LIGO/VIRGO-Coll.(2019), LIGO/VIRGO-Coll.(2021), LIGO/VIRGO-Coll. (2024), LIGO/VIRGO/KAGRA-Coll. (2023)] support such a scenario. In [Biermann et al. (2018)] we suggested that stellar mass black hole mergers (visible in M82: [Kronberg et al. (1985), Allen & Kronberg (1998), Allen (1999), Biermann et al. (2018)]) with an associated spin-flip [Gergely & Biermann (2009)]analogously allow the acceleration of energetic particles, with ensuing high energy neutrinos and high energy photons, and finally producing gravitational waves. At cosmic distances only the gravitational waves and the neutrinos remain detectable. Here we generalize the argument to starburst and normal galaxies throughout their cosmic evolution, and show that these galaxies may dominate over Active Galactic Nuclei (AGN) in the flux of ultra-high energy particles observed at Earth. All these sources contribute to the cosmic neutrino background [Jaroschewski (2023a), Jaroschewski et al. (2023b)], as well as the gravitational wave background ([NanoGrav-Coll. (2023a), NanoGrav-Coll. (2023b), NanoGrav-Coll. (2023c)]; they detected the lower frequencies). We outline a search strat-